PENGARUH MODEL PEMBELAJARAN PROCESS ORIENTED GUIDED INQUIRY LEARNING TERHADAP KETERAMPILAN PROSES SAINS PADA MATERI HUKUM ARCHIMEDES DI KELAS VIII SMPN 2 MARIORIWAWO - Magfirah, Siti; Umar Dani, Ali; Hasrianti, Andi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to determine students' science process skills in POGIL and conventional learning and to examine the effect of the POGIL model on science process skills in learning Archimedes' Principle. This study employed a quantitative quasi-experimental method using the Nonequivalent Posttest-Only Control Group Design. The sample consisted of an experimental class and a control class. Data were collected using a science process skills test and an observation sheet. The results of the independent samples t-test showed a significance value of Sig. (2-tailed) < 0.001, indicating that the POGIL model had a significant effect on students' science process skills.